2020
DOI: 10.3389/fmed.2020.563094
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and Fetal Outcomes of Pregnancy in Nephrotic Syndrome Due to Primary Glomerulonephritis

Abstract: Chronic kidney disease (CKD) affects 3% of pregnancies, impacting on maternal and fetal outcomes, and at the same time, a recurrent question in nephrology regards gestation impact on kidney function. Observational studies stated that CKD stage, pre-existent hypertension, and proteinuria are the main predictors of possible complications, such as maternal CKD progression, maternal or fetal death, prematurity, small for gestational age (SGA) newborn, or admission to the neonatal intensive care unit. In this regar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…[ 14 ] Studies conducted in Turkey suggest that DKD exhibits a higher prevalence in women compared to men, which was consistent with the results of the current study (Siligato et al ., 2020). [ 15 ] However, the previous research has shown mixed results, with 38 studies reporting a higher incidence of CKD in women and 13 studies reporting a higher prevalence in men (Hill et al ., 2016). [ 16 ] Furthermore, in contrast to these findings, males appear to have a greater risk of progressing to CKD (Ricardo et al ., 2019)[ 17 ] (Pugliese et al ., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…[ 14 ] Studies conducted in Turkey suggest that DKD exhibits a higher prevalence in women compared to men, which was consistent with the results of the current study (Siligato et al ., 2020). [ 15 ] However, the previous research has shown mixed results, with 38 studies reporting a higher incidence of CKD in women and 13 studies reporting a higher prevalence in men (Hill et al ., 2016). [ 16 ] Furthermore, in contrast to these findings, males appear to have a greater risk of progressing to CKD (Ricardo et al ., 2019)[ 17 ] (Pugliese et al ., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Gender-related differences have been reported in non-diabetic chronic kidney disease (CKD) [ 8 ]. Overall, CKD seems to have a higher prevalence in women than in men [ 9 , 10 , 11 ]. However, a review including a large number of studies found 38 studies reporting a higher CKD prevalence in women and 13 among men [ 12 ].…”
Section: Gender Differences In the Prevalence Of Dkd And Its Phenotypesmentioning
confidence: 99%
“…Age at conception ≥ 38 years tended to have an increased association with maternal complications compared to ≤ 37 years, but neonatal complications developed in mothers whose ages were 32, 33 and 39 years. Furthermore, malnutrition suggested by sAlb ≤ 3.2 mg/dL in the first trimester appears to be a common risk for both maternal and neonatal complications [ 16 , 17 ]. These complex findings are in line with a previous report by Villar et al which proposed that preeclampsia (as a maternal complication) and FGR (as a neonatal complication) may have distinct etiologies among obstetric disorders [ 18 ].…”
Section: Discussionmentioning
confidence: 99%